2020
DOI: 10.1016/j.jemermed.2020.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Best Practice Recommendations for Point-of-Care Lung Ultrasound in Patients with Suspected COVID-19

Abstract: Background: Lung point-of-care ultrasound (POCUS) is a critical tool for evaluating patients with dyspnea in the emergency department (ED), including patients with suspected coronavirus disease (COVID)-19. However, given the threat of nosocomial disease spread, the use of ultrasound is no longer risk free. Objective: Here, we review the lung POCUS findings in patients with COVID-19. In doing so we present a scanning protocol for lung POCUS in COVID-19 that maximizes clinical utility and provider safety. Discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…Characteristic findings of the COVID-19 syndrome on lung POCUS include a thickened or irregular pleural line, confluent B-lines, and subpleural consolidations [ 19 , 21 23 ]. These findings correlate closely with those observed on CT [ 22 ], and demonstrate promise in trending clinical progression from onset to peak to resolution [ 21 , 24 ]. Descriptive studies [ 25 31 ] have revealed the potential utility of lung POCUS but are limited by small sample sizes, lack of in-depth statistical analysis, and limited evaluation of patient characteristics that impact the utility of lung POCUS.…”
Section: Introductionsupporting
confidence: 79%
“…Characteristic findings of the COVID-19 syndrome on lung POCUS include a thickened or irregular pleural line, confluent B-lines, and subpleural consolidations [ 19 , 21 23 ]. These findings correlate closely with those observed on CT [ 22 ], and demonstrate promise in trending clinical progression from onset to peak to resolution [ 21 , 24 ]. Descriptive studies [ 25 31 ] have revealed the potential utility of lung POCUS but are limited by small sample sizes, lack of in-depth statistical analysis, and limited evaluation of patient characteristics that impact the utility of lung POCUS.…”
Section: Introductionsupporting
confidence: 79%
“…It has an overall diagnostic sensitivity and specificity of 90.2% (67.6–99.3%) and 88.8% (81.8–94.4%) in COVID-19 pneumonia when compared to CXR, CT and clinical exam [ 25 ]. Additionally, while COVID-19 has a preference to affect the posterior-basal lung zones, ultrasound provides effective visualization of the lung’s peripheries [ 10 , 26 30 ]. LUS is not capable of visualising central lung lesions—these are best seen on cross-sectional CT imaging.…”
Section: Methodsmentioning
confidence: 99%
“…Their guideline provide detail descriptions of anatomical landmarks, imaging settings, and presented a scoring mechanism. Meanwhile, experts in the US have developed a six‐zone POCUS protocol that prioritize provider safety that optimizes provider positioning and minimizes the time spent scanning 85 . Their protocol mainly focuses on imaging the posterior and lateral lung fields, arguing that scanning anteriorly is not necessary to obtain clinically useful data 85 .…”
Section: Current Guidelines and Recommendations For Covid‐19 Patientsmentioning
confidence: 99%
“…Meanwhile, experts in the US have developed a six‐zone POCUS protocol that prioritize provider safety that optimizes provider positioning and minimizes the time spent scanning 85 . Their protocol mainly focuses on imaging the posterior and lateral lung fields, arguing that scanning anteriorly is not necessary to obtain clinically useful data 85 . This was supported by a study of 20 COVID‐19 patients where most lung pathology was found primarily in the posterior lung bases 47 …”
Section: Current Guidelines and Recommendations For Covid‐19 Patientsmentioning
confidence: 99%
See 1 more Smart Citation